Influence of Internal Clearance Variation of Semi-floating Ring Bearing on Vibration Response of Electrically Assisted Turbocharger Rotor System - Baoyin Duan; Chuanlei Yang; Hua Shen; Hechun Wang; Yinyan Wang (Journal of Low Frequency Noise, Vibration and Active Control)
As an emerging technology, electrically assisted turbocharging (EAT) technology can effectively solve the problem of turbo lag of traditional turbochargers. The turbocharger (TC) rotor was discretized to establish a finite element model and its effectiveness was verified based on experiments, and then the EAT rotor design was carried out. The linear and nonlinear dynamic analysis of EAT rotor semi-floating floating ring bearing (SFRB) system is carried out. The results show that the critical speed of EAT rotor is lower than that of TC rotor. The larger internal clearance will cause strong sub-synchronous vibration of the EAT rotor in the low-speed stage. Properly reducing the internal clearance can effectively suppress the sub-synchronous vibration at low speed, and the high-speed rotor performs balanced motion on the “critical limit cycle.” Taking the EAT with low vibration noise and efficient operation as the goal, it is recommended to keep the inner clearance size at about 0.315 mm.